Differences in wood properties among Eucalyptus grandis and Eucalyptus grandis x Eucalyptus urophylla with different degrees of ploidy (Research, Society and Development, 2021)
We compared the anatomy, density, chemical contents, and bioenergy values of Eucalyptus grandis and hybrids of Eucalyptus grandis x Eucalyptus urophylla wood originating from diploids, triploids and tetraploids. We hypothesize that Eucalyptus grandis and hybrids of Eucalyptus grandis x Eucalyptus urophylla with different degrees of ploidy have variations as a result of different sets of chromosomes producing different phenotypic expressions and chemical constituents, such as variation in cell size and frequency, which would directly influence wood quality. Twenty-year-old trees were cut, eight for each ploidy: diploids and tetraploids are E. grandis; triploids are E. grandis x E. urophylla. We use standardized techniques. Our hypothesis was confirmed. Triploid and tetraploid trees presented wider trunks, taller trees with longer stems and wider crowns compared to diploid trees. Wood density showed significant radial variation only in diploids, while triploid and tetraploid trees were more homogeneous. In polyploid trees, the anatomical features did not clearly present a radial pattern. Triploid and tetraploid trees presented higher density wood than diploid trees. The chemical constituents varied from pith to bark in the three ploidies, but no differences between ploidies were found. For energy generation purposes, diploid and triploid trees are more desirable than tetraploid trees.